Salaam : development as mission - Giordano, Christian, 1956-; Pérez, Charo (Regnum global voices, 2022)
In a world where violence, polarization, and wars abound, to speak of a theology of "development-salam" is an invitation to be ambassadors of peace and reconciliation, and at the same time to be a prophetic voice denouncing injustice and oppression in its most diverse expressions. This text is an invitation to develop an integral incarnational ministry that gestates deep and transformative changes in all dimensions of life through genuine and reconciled relationships from our vulnerability and dependence on the God of Mission.